ANALYSIS OF USING NEW TECHNOLOGY OF FORMATION ACIDIC FRACTURING OF TERRIGENOUS COLLECTORS - Качмар, Юрій Дмитрович; Цьомко, Володимир Васильович; Климович, Ігор Федорович; Заливаха, Ярослав Опанасович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The disclosure and development of fractures during interval action by acids on single formation and action on the whole multiple-zone drill core of wells are analyzed. The fractures sizes, sizes of dissolution zones rocks in the fracture and around them in such conditions are detected. An example of acidic fracturing in multiple-zone drill core of wells is presented. The results of new technology using are showing.